(3JdbjM GdYbhds - (3HQjg Hf CHj GdHTQ (B((3GdjSQ(B) (3GdQjGVj,J (B341 (3g` s ((3eMeO Hf CMeO Hf EHQGgje GdCcQei GdTGei GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe Ydi GdEfSGf ef Hjf LejY GdMjhGf HaVjdI GdHjGf hLYd GdJejjR ai GdCPgGf s
(3BNQgG (B:s
(3Je cJGH JdbjM GdYbhd HMeO Gddg hYhfg hGdMeO ddg hMOgq s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs